Behavioral Interventions in Six Dimensions of Wellness That Protect the Cognitive Health of Community‐Dwelling Older Adults: A Systematic Review. Issue 5 (10th May 2016) - Strout, Kelley A.; David, Daniel J.; Dyer, Elizabeth J.; Gray, Roberta C.; Robnett, Regula H.; Howard, Elizabeth P.
Abstract : Objectives: To systematically identify, appraise, and summarize research on the effects of behavioral interventions to prevent cognitive decline in community‐dwelling older adults using a holistic wellness framework. Design: Systematic review of randomized controlled trials that tested the effectiveness of behavioral interventions within each of the six dimensions of wellness: occupational, social, intellectual, physical, emotional and spiritual. Databases searched included PubMed MEDLINE, EMBASE, CENTRAL, PsycINFO, CINAHL, ALOIS, and The Grey Literature Report through July 1, 2014. Setting: Community. Participants: Individuals aged 60 and older (N = 6, 254). Measurements: Consolidated Standards of Reporting Trials Checklist. Results: Eighteen studies met the inclusion criteria. Interventions in the physical dimension of wellness were most common (11 studies); interventions in the spiritual dimension were least common (0 studies). Fifty‐nine different measures were used to measure multiple cognitive domains, with memory being the most commonly measured (17 studies) and language being the least commonly measured (5 studies). Fifty percent of the interventions examined in the 18 studies demonstrated statistically significant outcomes on at least one cognitive measure. Interventions in the intellectual dimension that examined cognitively stimulating activities using pen and paper or a computer represented the greatest percentage of statistically significant outcomes. Conclusion: Intellectual and physical interventions were most studied, with varied results. Future research is needed using more‐consistent methods to measure cognition. Researchers should include the National Institutes of Health Toolbox Cognition Battery among measurement tools to facilitate effective data harmonization, pooling, and comparison.